New Type of Neutrosophic Points (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Through the presentation of [1]  in his research about Neutrosophic set theory as well as through his definition of Neutrosophic points . We have shown that it doesn’t make its sets through the union which defined by the researcher . so we need to define Neutrosophic point which achieved principle that the set represents its union points by definition an union which serve this principle as well as integration of Neutrosophic point in the Neutrosophic topological spaces and defined (interior, exterior, boundary limit and closure) points.